The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18433/j3gp6g
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Nanoparticle Coating of Dental Implants for Enhanced Osseointegration and Antimicrobial Purposes

Abstract: -PURPOSE: Nanomaterials are suitable candidates for coating of titanium based (Ti-based) dental implants due to their unique properties. The objective of this article is to summarize the application of nanoparticles as Ti-based implant coating materials in order to control and improve the implant success rate with focus on enhanced osseointegration and antimicrobial purposes. METHOD: This review was conducted using electronic databases and MeSH keywords to detect associated scientific literature published in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 39 publications
0
56
0
Order By: Relevance
“…at a concentration of 0.2 μg/mL, which is markedly less than the concentration (30 μg/mL) required to demonstrate a toxic effect against human fibroblasts [128]. Besides, it has been reported that by incorporating AgNPs into titanium implant material, not only the antibacterial ability of the implant is enhanced, but also the surface remains biocompatible [129]. Similarly, nZnO has been shown to possess good biocompatibility.…”
Section: Biocompatibility Of Nanoantimicrobials Within the Oral Cavitymentioning
confidence: 99%
“…at a concentration of 0.2 μg/mL, which is markedly less than the concentration (30 μg/mL) required to demonstrate a toxic effect against human fibroblasts [128]. Besides, it has been reported that by incorporating AgNPs into titanium implant material, not only the antibacterial ability of the implant is enhanced, but also the surface remains biocompatible [129]. Similarly, nZnO has been shown to possess good biocompatibility.…”
Section: Biocompatibility Of Nanoantimicrobials Within the Oral Cavitymentioning
confidence: 99%
“…Coating of bioinert materials with ability to encourage osseointegration on the titanium implant surfaces in order to improve the stability of them has been reported by different investigators (Samiei et al 2016;Parnia et al 2017). Based on the related literature, different types of biomaterials have used as particle coatings to the dental implant surface to progress soft tissue integration and therefore enhance dental implants success.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The implant insertion may also expose in risk to bacterial plaque (Samiei et al 2016;Parnia et al 2017). The reports have shown that dental implants are at an enlarged risk of microbial contamination due to continuously colonization of microorganisms in the oral cavity.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles have shown significant potential to provide a platform for targeted delivery of drugs because of their unique multi-functionality. Delivering and targeting of drug to its intended site are the most important characteristics of nanoparticles [4,[23][24][25].…”
Section: Nanoparticulate Systems For Treatment and Diagnosis Of Cvdsmentioning
confidence: 99%